2021
DOI: 10.1002/app.51574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of size, concentration, and nature of fillers on crystallinity, thermal, and mechanical properties of polyetheretherketone composites

Abstract: Polyetheretherketone (PEEK) composites exhibit high stiffness, chemical stability, and heat resistance and they are therefore employed in applications under severe operating environments. This work aims to provide insight into the effect of the size, concentration, and type of fillers on the thermal and mechanical properties of PEEK. A total of 32 composites are used to highlight the influence of nature (lamellae, such as boron nitride and graphite and silicon carbide and alumina), size (nano and micrometric),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 66 publications
(104 reference statements)
0
17
0
Order By: Relevance
“…The graphene concentration of the graphene/epoxy nanocomposites is an essential factor influencing TC. In the literature, , the study on graphene concentration is performed by increasing the number of graphene sheets in a certain epoxy matrix. The TC of the nanocomposites is influenced by both the concentration and arrangement of graphene. , Here, the influence of graphene concentration on TC is investigated first to identify the graphene mass fraction in the RVE model for subsequent studies.…”
Section: Resultsmentioning
confidence: 99%
“…The graphene concentration of the graphene/epoxy nanocomposites is an essential factor influencing TC. In the literature, , the study on graphene concentration is performed by increasing the number of graphene sheets in a certain epoxy matrix. The TC of the nanocomposites is influenced by both the concentration and arrangement of graphene. , Here, the influence of graphene concentration on TC is investigated first to identify the graphene mass fraction in the RVE model for subsequent studies.…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that the %XC decreased with increasing filler contents, which could have been due to the restricted mobility of the UHMWPE molecular chains caused by the addition of the Sm 2 O 3 and Gd 2 O 3 particles that retarded growth in the crystalline phase and subsequently lowered the %XC of the UHMWPE composites 33 . It was also observed that the Gd 2 O 3 /UHMWPE composites had slightly lower %XC values than those of Sm 2 O 3 /UHMWPE composites at the same filler content, probably due to Gd 2 O 3 having a slightly larger particle size, as well as a greater content of KBE903 than those of Sm 2 O 3 , resulting in greater restriction in the Gd 2 O 3 molecular chains to mobilize and grow crystalline phase 34 …”
Section: Resultsmentioning
confidence: 92%
“…Internal air gaps are detected between deposited rasters for copper, brass, and tungsten-filled PLA specimens. It is reported 40 that filler material addition to base polymer may increase the overall viscosity of melted filament during deposition process. Even if the infill density is kept at 100%, air gaps occurred in the intersections which can be attributed to the filler effect on polymer viscosity.…”
Section: Resultsmentioning
confidence: 99%